1996
DOI: 10.1007/bf02483351
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of efficacy and optimal dose of intraoperative glucose in rabbits under general anesthesia

Abstract: This experimental study was designed to investigate the efficacy of glucose loading during surgery. Rabbits, fasted overnight, received 20 ml·kg·h fluid infusion containing glucose at various concentration (0,0.5, 1.0, 1.5, 2.0% w/v) for 3 h intraoperatively. Plasma glucose level increased after the beginning of operation, but the increase was slight in groups given 0.2 g·kg·h or lower doses of glucose. Glucose at higher doses caused marked hyperglycemia. These higher doses also promoted urinary glucose excret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 7 publications
(5 reference statements)
2
8
0
Order By: Relevance
“…For example, it is often low during trauma, surgery, and other states. In a previous study we confirmed that alterations can be induced in the glucose tolerance limit by demonstrating that administration of no glucose caused an intraoperative increase in plasma glucose level [5], and in the present study by demonstrating that plasma glucose level does not change with infusion of 0.2 g·kg Ϫ1 ·h Ϫ1 glucose or less.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…For example, it is often low during trauma, surgery, and other states. In a previous study we confirmed that alterations can be induced in the glucose tolerance limit by demonstrating that administration of no glucose caused an intraoperative increase in plasma glucose level [5], and in the present study by demonstrating that plasma glucose level does not change with infusion of 0.2 g·kg Ϫ1 ·h Ϫ1 glucose or less.…”
Section: Discussionsupporting
confidence: 92%
“…However, in many circumstances, intraoperative glucose administration may be advantageous to inhibit catabolism and improve fat and carbohydrate metabolism [2][3][4]. Our previous animal study also showed that intraoperative glucose supplementation is effective in preventing hepatic glycogen depletion, and indicated further that the optimal dose to avoid glucose overloading was 0.1-0.2 g·kg Ϫ1 ·h Ϫ1 [5]. These findings confirm the necessity of intraoperative glucose infusion in clinical settings.…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…Accordingly, it is thought to be reasonable to administer a glucose solution to patients before [1] and during anesthesia to replenish the fuel level [2].…”
mentioning
confidence: 99%
“…In patients undergoing major surgery or who are critically ill, several investigators have suggested that the use of smaller doses of glucose could prevent unexpected harmful effects [2,8].…”
mentioning
confidence: 99%